Some solutions to the problem of grain mold in sorghum: a review - Chandrashekar, A.; Shewry, P.R.; Bandyopadhyay, Ranajit (2000)
Grain mold of sorghum (sorghum bicolor (L.) Moench result from colonization of fungi in the developing grain towards the end of the growing season, being often associated with late rains. The major colonizing fungi (fusarium thapsinum Klittch, leslie, Nelson at Marasas sp. Nov., Curvularia lunata (wakker)